Artificial Intelligence in Islamic Religious Education: Balancing Learning Efficiency And Safeguarding Spiritual Integrity In Indonesian Higher Education - Nazih Sadatul Kahfi; Fadilla Arfa Reyza; Mayam Arrosikha; Mochammad Nasrullah; Nagita Histimuna Aisyah (INJECT (Interdisciplinary Journal of Communication), 2025)
Technological advances, including artificial intelligence (AI), are starting to be applied in Islamic Religious Education. However, the integration of AI in PAI needs to be taken seriously because the aims of PAI do not only include cognitive aspects, but also the formation of character and spiritual values ​​in accordance with Islamic teachings. This research aims to explore the potential of AI in PAI, identify challenges that may arise, and formulate strategies to maintain a balance between technological advances and religious values. The research method used is descriptive qualitative with a case study approach to analyze the role of AI in the PAI learning context. The research results show that AI can increase the accessibility of teaching materials by adapting to students' local and cultural contexts, as well as increasing student engagement in the learning process. However, a special strategy is needed to ensure that AI integration remains in line with Islamic values, including: (1) Integration of AI systems with a framework that is guided by Islamic principles, and (2) Development of AI based on religious ethics. This research recommends further empirical studies to measure the effectiveness of using AI in PAI learning.